Different Radiological Criteria for Early Tumor Response Evaluation in Patients With Unresectable Hepatocellular Carcinoma Treated With Anti-PD-1 Antibody Plus Bevacizumab - Xu, Ying; Yang, Yi; Li, Lu; Zhou, Aiping; Zhang, Hongmei; Ye, Feng; Zhang, Wen; Zhao, Hong; Zhao, Xinming (Frontiers in Oncology, 2022)
Objectives: To compare different radiological criteria in evaluating early tumor response for patients with unresectable HCC (uHCC) treated with anti-programmed cell death protein 1 (PD-1) antibody plus bevacizumab. Methods: From October 2018 to January 2020, 58 patients [age: 55.2 ± 10.6 years, 49 (84.5%) males] receiving both anti-PD-1 antibody and bevacizumab were retrospectively included. Pre- and the first post-treatment contrast-enhanced computed tomography (CE-CT) scans were performed in all patients. RECIST 1.1, mRECIST, Choi and revised Choi (rChoi) criteria were applied to evaluate tumor response. Endpoint events were defined as overall survival (OS). Results: Six (10.3 %), 9 (15.5%), 30 (51.7%), 12 (20.7%) patients were diagnosed as responders by RECIST 1.1, mRECIST, Choi and rChoi, respectively. RECIST 1.1 and mRECIST criteria failed to correlate evaluation categories with OS ( p = 0.130, 0.253, respectively), while both Choi and rChoi significantly correlated with OS ( p = 0.002, 0.006, respectively). Among the four criteria, only patients identified as responders by Choi ( p = 0.0005) and rChoi ( p = 0.005) showed significantly better OS than non-responders. The cumulative 1-year, 2-year OS rates were 93.3%, 79.8% in responders and 69.3%, 30.3% in non-responders by Choi, 100.0%, 100.0% in responders and 74.9%, 43.1% in non-responders by rChoi, respectively. Conclusions: The early tumor response evaluation by Choi and rChoi instead of RECIST 1.1 and mRECIST significantly corelated with OS for patients with uHCC treated with anti-PD-1 antibody plus bevacizumab. Moreover, patients identified as responders by Choi and rChoi showed significantly better OS than non-responders.